An engineer$1 (Bs guide to MATLAB : s with applications from mechanical, aerospace, electrical, civil, and biological systems engineering - Magrab, Edward B. (Upper Saddle River, N.J. : Prentice Hall, 2011)
An Engineer's Guide to MATLAB, 3/e, is an authoritative guide to generating readable, compact, and verifiably correct MATLAB programs. It is ideal for undergraduate engineering courses in Mechanical, Aeronautical, Civil, and Electrical engineering that require/use MATLAB. This highly respected guide helps students develop a strong working knowledge of MATLAB that can be used to solve a wide range of engineering problems. Since solving these problems usually involves writing relatively short, one-time-use programs, the authors demonstrate how to effectively develop programs that are compact yet readable, easy to debug, and quick to execute. Emphasis is on using MATLAB to obtain solutions to several classes of engineering problems, so technical material is presented in summary form only.
Vectors and matrices / Edward B. Magrab -- Data input/output / Edward B. Magrab -- Program flow control / Edward B. Magrab -- Function creation and selected MATLAB functions / Edward B. Magrab -- 2D graphics / Edward B. Magrab -- 3D graphics / Edward B. Magrab -- Engineering statistics / Edward B. Magrab -- Dynamics and vibrations / Balakumar Balachandran -- Control systems / Gregory
Includes index.
1
Keywords: Engineering mathematics -- Data processing; MATLAB